Anaesthetic management of an emergency caesarean section in a complex immunologically compromised patient with pre‐eclampsia and multifactorial thrombocytopaenia. Issue 2 (16th October 2020) - Judge, A.; O'Shaughnessy, S.; McCaul, C.
Summary: A 35‐year‐old gravida 3, para 0 woman required an emergency caesarean section for pre‐eclampsia with severe features including a platelet count of 7 × 10 9 .l −1 . The patient's thrombocytopaenia was an acute on chronic presentation. In addition to pre‐eclampsia, the patient had a complex background history which included autoimmune lymphoproliferative syndrome, the manifestations of which include autoimmune cytopaenias and recurrent infections. The patient also had common variable immune deficiency and acquired C1‐esterase inhibitor deficiency which may cause life‐threatening angioedema, including of the airway. In this report, we describe the potential anaesthetic challenges posed by this pre‐eclamptic, immunologically compromised patient with severe thrombocytopaenia and the potential for difficult airway, and how these were addressed in a safe and timely manner. Specifically, we highlight the important considerations when performing a general anaesthetic in this unique combination of circumstances. Although the patient's conditions are rare, this case demonstrates that early multidisciplinary team input can help successfully guide the management of medically complex pregnant patients.